УДОСКОНАЛЕННЯ СТРУКТУРИ КОНТУРА РЕГУЛЮВАННЯ СТРУМУ З ВИКОРИСТАННЯМ ШІМ ДЛЯ МЕРЕЖЕВОГО ІНВЕРТОРА КОМБІНОВАНОЇ СИСТЕМИ ЕЛЕКТРОЖИВЛЕННЯ - Шавьолкін, О.О. (Інститут електродинаміки НАН України, Київ, 2019)
Based on the analysis of the principle of current formation of a single-phase a grid bridge inverter for combined power system with combining the function of the active filter, there are opportunities to improve the structure of the output current control loop with PWM by reducing of the error in forming the output current to improve the harmonic compositionof the grid current in the presence of non-linear load. The dependences for the amplitude of current pulsations and error for the main current harmonic are obtained in accordance with the inverter input voltage, modulation frequency and reactor inductance. It was found that for the harmonically law of variation of the derivative of the referenceof current, the error in the formation of current is constant and is determined by the first harmonic of the grid voltage. The static compensation of the error according to the main harmonic of the current and the dynamic compensation of the current waveform distortion for nonlinear load are substantiated. The structure of the control system has been improvedwith the introduction of compensating circuits. The results of modeling the system “a grid - inverter - load” are given. References 11, figures 6.